All-solid-state lithium battery containing composite binder and preparation method of all-solid-state lithium battery
The use of a composite binder composed of ethylene-vinyl acetate copolymer and polyvinylidene fluoride addresses the brittle nature of sulfide solid electrolytes in all-solid-state lithium batteries, enhancing cycle stability and structural integrity by ensuring consistent volume change and flexibility, thus improving battery performance.
Patent Information
- Application Number
- CN202411365639.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-20
AI Technical Summary
Sulfide solid electrolytes in all-solid-state lithium batteries are prone to cracking and stretching during battery cycling, leading to poor interfacial contact, increased impedance, and reduced cycle stability due to their brittle nature, which limits the energy density and structural integrity of the batteries.
A composite binder composed of ethylene-vinyl acetate copolymer and polyvinylidene fluoride is used in the positive and negative electrode sheets and solid electrolyte layers, providing adhesion, high temperature resistance, and mechanical stability, ensuring consistent volume change and flexibility during charging and discharging, thereby enhancing cycle stability and structural integrity.
The composite binder ensures stable and efficient long-term cycle performance by maintaining consistent volume change, flexibility, and mechanical strength, reducing internal stress, and improving the battery's cycle stability and structural integrity.
Smart Images

Figure CN119170802A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of all-solid-state energy storage devices and relates to an all-solid-state lithium battery containing a composite binder and a preparation method thereof. Background Art
[0002] All-solid-state lithium batteries, which use inorganic solid electrolytes with high ionic conductivity to replace the electrolyte and diaphragm in traditional lithium-ion batteries, have doubled energy density while ensuring high safety. They are new energy storage batteries or power batteries with broad application prospects. Among many solid electrolytes, sulfide solid electrolytes have become one of the solid electrolytes with great commercial potential due to their relatively high ionic conductivity, low grain boundary impedance and good machinability.
[0003] Although sulfide solid electrolytes have many advantages, their hard and brittle properties limit their practical applications. In order to prevent the solid electrolyte layer from breaking during battery assembly, it is usually necessary to press it into a sheet structure with a thickness between several hundred microns and about 1 mm. Such thickness increases the overall weight of the battery, making the energy density of most all-solid-state lithium batteries far lower than expected. Therefore, the thin filmization of solid electrolytes is the key to assembling high-energy-density all-solid-state lithium batteries.
[0004] Solid electrolyte membranes and positive and negative electrode sheets based on traditional binders are prone to cracking and stretching during battery cycling, which in turn causes failure of all-solid-state lithium batteries. Electrode sheets are also prone to volume expansion, resulting in pores, cracks, poor contact and other phenomena at the interface, increasing interfacial impedance and affecting the long-term cycle capacity of the battery. Therefore, developing a binder with excellent performance to prepare flexible and stable solid electrolyte membranes and positive and negative electrode sheets is an important direction to improve the energy density and cycle stability of all-solid-state lithium batteries. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an all-solid-state lithium battery containing a composite binder and a preparation method thereof. Ethylene-vinyl acetate copolymer and polyvinylidene fluoride are used as binders in the all-solid-state lithium battery to ensure stable and efficient long-term cycle performance of the battery.
[0006] One object of the present invention is achieved by the following technical solutions: An all-solid-state lithium battery containing a composite binder comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, wherein the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer all comprise a composite binder, and the composite binder is ethylene-vinyl acetate copolymer and polyvinylidene fluoride.
[0007] The present invention uses ethylene-vinyl acetate copolymer and polyvinylidene fluoride in different mass ratios as binders, and the advantages of the two are complementary, so that the composite binder has good adhesion, high temperature resistance, chemical corrosion resistance, excellent mechanical properties and high stability with solid electrolytes, and the prepared solid electrolyte film has a lower impedance value and higher ionic conductivity. The composite binder is applied to the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer at the same time. Due to the rubber properties of the ethylene-vinyl acetate copolymer, the solid electrolyte membrane and the positive and negative electrode sheets show excellent flexibility, which can alleviate the volume change during the battery charging and discharging process, and ensure stable and efficient long-term cycle stability; at the same time, the introduction of the polyvinylidene fluoride binder can ensure that the various substances are evenly dispersed during the pulping process, enhance the bonding force between the particles, provide a strong bonding force between the material and the substrate, and realize a sulfide solid electrolyte film and positive and negative electrode sheets with good mechanical strength and stability. In addition, the all-solid-state battery assembled with the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer prepared by the composite binder has significantly enhanced electrochemical properties. The application of composite binders in the positive electrode sheet, negative electrode sheet and solid electrolyte layer ensures that the volume change, flexibility and mechanical strength of each component of the battery remain consistent during the charging and discharging process, effectively alleviating the internal stress caused by inconsistent volume expansion / contraction, and improving the battery's cycle stability and structural integrity.
[0008] Preferably, in the composite binder, the mass ratio of ethylene-vinyl acetate copolymer to polyvinylidene fluoride is 0.1:99.9~99.9:0.1.
[0009] More preferably, in the composite binder, the mass ratio of ethylene-vinyl acetate copolymer to polyvinylidene fluoride is 5:95 to 95:5.
[0010] Preferably, the positive electrode plate comprises a current collector and a positive electrode material layer located above the current collector, and the positive electrode material layer comprises a positive electrode active material, a conductive agent and a composite binder.
[0011] More preferably, the positive electrode material layer includes a positive electrode active material, a sulfide solid electrolyte, a conductive agent and a composite binder.
[0012] Preferably, in the positive electrode material layer, the mass proportion of the composite binder is 0.1-10wt%.
[0013] Further preferably, in the positive electrode material layer, the mass proportions of the positive electrode active material, the sulfide solid electrolyte, and the conductive agent are 60-80wt%, 20-40wt%, and 0.5-5wt%, respectively.
[0014] Preferably, the negative electrode plate comprises a current collector and a negative electrode material layer located above the current collector, and the negative electrode material layer comprises a negative electrode active material, a conductive agent and a composite binder.
[0015] More preferably, the negative electrode material layer includes a negative electrode active material, a sulfide solid electrolyte, a conductive agent and a composite binder.
[0016] Preferably, in the negative electrode material layer, the mass proportion of the composite binder is 0.1-10wt%.
[0017] More preferably, in the negative electrode material layer, the mass proportions of the negative electrode active material, the sulfide solid electrolyte, and the conductive agent are 50-70wt%, 30-50wt%, and 0.5-5wt%, respectively.
[0018] Preferably, the solid electrolyte layer comprises a sulfide solid electrolyte and a composite binder.
[0019] More preferably, in the solid electrolyte layer, the mass proportion of the composite binder is 0.1-10wt%.
[0020] Preferably, the sulfide solid electrolyte is one or a mixture of sulfide solid electrolytes having the general formula I, II or III: Li 6±l P 1-e E e S 5-r R r X 1±t Formula I, In formula I, 0≤l<1, 0≤e<1, 0≤r<1, 0≤t<1, E is one or more of Ge, Si, Sn, Sb, R is O and / or Se, and X is one or more of F, Cl, Br, I; Li 10±l Ge 1-g G g P 2-q Q q S 12-w W w Formula II, In formula II, 0≤l<1, 0≤g≤1, 0≤q<2, 0≤w<1, G is Si and / or Sn, Q is one or more of Sb, As, Ti, and W is one or more of O, Se, F, Cl, Br, and I; (100-xy)Li 2 S.xP 2 S 5 ·yM m N n Formula III, In formula III, 0≤x<100, 0≤y<100, 0<x+y<100, 0≤m<4, 0≤n<6, M is one or more of Ge, Si, Sn, Sb, and N is one or more of Se, O, Cl, Br, and I.
[0021] The sulfide solid electrolyte in the solid electrolyte film and the positive and negative electrode sheets of the present invention has the chemical formula shown in the above formula I, formula II or formula III. The ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder has higher stability in the sulfide solid electrolyte, which is beneficial to improving the ionic conductivity of the electrolyte film and more beneficial to improving the cycle performance of the battery.
[0022] Preferably, the positive electrode active material is a lithium transition metal oxide, which can be exemplified by LiCoO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 One or more of the above.
[0023] The negative electrode active material is not particularly limited, and any material that can be used to store lithium ions in an all-solid-state lithium battery can be used, and can be one or more of graphite, hard carbon, pure silicon, silicon-carbon composite materials, and the like.
[0024] The conductive agent is not particularly limited, and can be applied to the positive electrode sheet or the negative electrode sheet to improve the conductivity of the electrode, and can be one or more of carbon black, graphene, carbon nanotubes, carbon fibers, etc. Preferably, the method for preparing the solid electrolyte layer comprises the following steps: adding the composite binder solution and the sulfide solid electrolyte to an organic ester solvent, mixing them in a closed container, and dispersing them uniformly to obtain a sulfide solid electrolyte slurry; coating the sulfide solid electrolyte slurry on a substrate, drying it, and pressing it to obtain a sulfide solid electrolyte film.
[0025] The solid electrolyte layer is a stack of one or more layers of the above-mentioned sulfide solid electrolyte thin films.
[0026] The preparation method of the composite binder solution comprises: dissolving ethylene-vinyl acetate copolymer and polyvinylidene fluoride in an organic ester solvent to obtain the composite binder solution. Preferably, in the composite binder solution, the mass proportion of the composite binder is 2-10wt%.
[0027] Preferably, the thickness of the sulfide solid electrolyte film is 5 to 200 μm, more preferably 15 to 75 μm.
[0028] Preferably, the ionic conductivity of the sulfide solid electrolyte film at 25°C is 0.01-10 mS cm -1 , more preferably 1~5 mS cm -1 .
[0029] Preferably, the method for preparing the positive electrode plate comprises the following steps: adding raw materials for preparing the positive electrode material layer into an organic ester solvent, mixing in a closed container, and dispersing evenly to obtain a positive electrode slurry; coating the positive electrode slurry on a substrate, and pressing to obtain a positive electrode plate after drying.
[0030] Preferably, the method for preparing the negative electrode plate comprises the following steps: adding raw materials for preparing the negative electrode material layer into an organic ester solvent, mixing in a closed container, and dispersing evenly to obtain a negative electrode slurry; coating the negative electrode slurry on a substrate, drying it, and then pressing it to obtain a negative electrode plate.
[0031] The raw materials for preparing the positive electrode material layer include positive electrode active material, conductive agent and composite binder solution.
[0032] Furthermore, the raw materials for preparing the positive electrode material layer include positive electrode active material, sulfide solid electrolyte, conductive agent and composite binder solution.
[0033] The raw materials for preparing the negative electrode material layer include negative electrode active material, conductive agent and composite binder solution.
[0034] Furthermore, the raw materials for preparing the negative electrode material layer include negative electrode active material, sulfide solid electrolyte, conductive agent and composite binder solution.
[0035] Preferably, the organic ester solvent is one or a mixture of ester solvents such as ethyl acetate, benzyl acetate, sec-butyl acetate, butyl butyrate, isobutyl butyrate, isobutyl isobutyrate, and butyl isobutyrate.
[0036] Preferably, the mixing method in the closed container is a mixture of one or more of mechanical shaking, mechanical stirring, roller milling, ball milling, ultrasonic dispersion, and agate mortar grinding, and the mixing time is 0.1 to 6 h.
[0037] Preferably, the substrate is one or more of aluminum foil, copper foil, steel plate, glass plate, PE substrate, PET substrate, or the substrate is an extended product of a coating on aluminum foil, copper foil, steel plate, glass plate, PE substrate or PET substrate.
[0038] Preferably, the drying method is vacuum drying, the drying temperature is 20-200° C., and the drying time is 0.01-12 h.
[0039] Another object of the present invention is achieved by the following technical solutions: A method for preparing an all-solid-state lithium battery containing a composite binder comprises the following steps: The composite binder solution and the sulfide solid electrolyte are added to an organic ester solvent, mixed in a closed container, and dispersed uniformly to obtain a sulfide solid electrolyte slurry; the sulfide solid electrolyte slurry is coated on a substrate, dried, and pressed to obtain a sulfide solid electrolyte film; The raw materials for preparing the positive electrode material layer are added to an organic ester solvent, mixed in a sealed container, and dispersed evenly to obtain a positive electrode slurry; the positive electrode slurry is coated on a substrate, dried, and then pressed to obtain a positive electrode sheet; Adding raw materials for preparing the negative electrode material layer into an organic ester solvent, mixing in a closed container, and dispersing evenly to obtain a negative electrode slurry; coating the negative electrode slurry on a substrate, drying it, and pressing it to obtain a negative electrode sheet; The positive electrode sheet, sulfide solid electrolyte film and negative electrode sheet are cut into corresponding sizes and shapes, stacked and assembled in sequence to form an all-solid-state lithium battery.
[0040] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses ethylene-vinyl acetate copolymer and polyvinylidene fluoride as a binder. This composite binder has good adhesion, high temperature resistance, chemical corrosion resistance, excellent mechanical properties and high stability with sulfide solid electrolyte.
[0041] (2) The rubber properties of the ethylene-vinyl acetate copolymer in the ethylene-vinyl acetate copolymer and polyvinylidene fluoride composite binder of the present invention endow the solid electrolyte membrane and the positive and negative electrode sheets with excellent flexibility, enabling them to alleviate the volume change during the battery charging and discharging process, thereby ensuring stable and efficient long-term cycle performance; the introduction of the polyvinylidene fluoride binder can ensure that the various substances are evenly dispersed during the pulping process, enhance the bonding force between the particles, provide strong bonding force between the material and the substrate, and realize a sulfide solid electrolyte film and positive and negative electrode sheets with good mechanical strength and stability.
[0042] (3) The composite binder of the present invention can be well dissolved in ester solvents and shows high stability for sulfide solid electrolytes. The solid electrolyte film manufactured thereby exhibits a low impedance value and a high ionic conductivity. When matched with high specific energy positive and negative electrode materials, a high energy density all-solid-state lithium battery can be prepared.
[0043] (4) The application of composite binders in the positive electrode sheet, negative electrode sheet and solid electrolyte layer ensures that the volume change, flexibility and mechanical strength of each component of the all-solid-state battery remain consistent during the charging and discharging process, effectively alleviating the internal stress caused by inconsistent volume expansion / contraction, and improving the battery's cycle stability and structural integrity.
[0044] (5) The solid electrolyte film and the positive and negative electrode sheets of the present invention are produced by a wet coating process, which is simple to operate, highly practical, and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Li of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention 6 PS 5 AC impedance spectrum of Cl sulfide solid electrolyte film; Figure 2 This is a battery cycle performance diagram of the all-solid-state battery of Example 1 of the present invention; Figure 3 This is a battery cycle performance diagram of the all-solid-state battery of Comparative Example 1 of the present invention; Figure 4 This is a battery cycle performance diagram of the all-solid-state battery of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0046] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0047] The ethylene-vinyl acetate copolymer used in Examples 1-8 was purchased from McLean Company with a product number of P815475; the polyvinylidene fluoride was purchased from McLean Company with a product number of 768741.
[0048] The ethylene-vinyl acetate copolymer used in Examples 9-13 was purchased from Sigma-Aldrich Company with a product number of 340502, and the polyvinylidene fluoride was purchased from Aladdin Biochemical Company with a product number of P302012.
[0049] Example 1 The ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution is obtained by dissolving 30 parts by weight of ethylene-vinyl acetate copolymer and 70 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending them, wherein the total mass proportion of the composite binder is 5 wt%.
[0050] The all-solid-state lithium battery of this embodiment includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer. The preparation methods of the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are as follows: (1) Preparation of sulfide solid electrolyte film: 98 parts by weight of Li 6 PS 5 The Cl electrolyte and 2 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 40 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform solid electrolyte slurry. The solid electrolyte slurry was coated on aluminum foil with an adjustable coater and transferred to a vacuum oven at 80 ° C for vacuum drying for 8 hours to obtain a sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder. The thickness of the prepared sulfide solid electrolyte film is 30 μm, and the impedance value at room temperature (25 ° C, the same below) is 1.4 Ω•mm -1 (See Figure 1 ), the calculated ionic conductivity is 2.73 mS cm -1 .
[0051] (2) Preparation of positive electrode: 70 parts by weight of LiCoO 2 , 30 parts by weight Li 6 PS 5 Cl electrolyte, 2 parts by weight of vapor grown carbon fiber (VGCF) and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a positive electrode sheet based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0052] (3) Preparation of negative electrode sheet: 60 parts by weight of graphite, 40 parts by weight of Li 6 PS 5 Cl electrolyte, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform negative electrode slurry. The above-mentioned negative electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a negative electrode sheet based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0053] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder and the positive and negative electrode plates were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 1000 cycles at 0.5 C with a capacity retention rate of 81.9%. The battery cycle performance is shown in Figure 2 .
[0054] Example 2 The difference between Example 2 and Example 1 is that the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution of Example 2 is obtained by dissolving 40 parts by weight of ethylene-vinyl acetate copolymer and 60 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending them, wherein the total mass proportion of the composite binder is 5 wt %. The rest is the same as Example 1.
[0055] The thickness of the prepared sulfide solid electrolyte film is 30 μm, and the room temperature impedance value is 1.44 Ω•mm -1 The calculated ionic conductivity is 2.65 mS cm -1 .
[0056] The sulfide solid electrolyte film and positive and negative electrode sheets based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 1000 cycles at 0.5 C, and the capacity retention rate is 80.1%.
[0057] Example 3 The difference between Example 3 and Example 1 is that the organic ester solvent in Example 3 is butyl butyrate, and the rest is the same as Example 1.
[0058] The thickness of the prepared sulfide solid electrolyte film is 20 μm, and the room temperature impedance is 1.2 Ω•mm -1The calculated ionic conductivity is 2.65 mS cm -1 .
[0059] The sulfide solid electrolyte film and positive and negative electrode sheets based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 800 cycles at 0.3 C, and the capacity retention rate is 85.8%.
[0060] Example 4 The difference between Example 4 and Example 1 is that the positive electrode active material of Example 4 is LiNi 0.6 Co 0.2 Mn 0.2 O 2 , the rest is the same as Example 1.
[0061] The thickness of the prepared sulfide solid electrolyte film is 30 μm, and the room temperature impedance value is 1.4 Ω•mm -1 The calculated ionic conductivity is 2.73 mS cm -1 .
[0062] The sulfide solid electrolyte film and the positive and negative electrode sheets based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 4 were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 800 cycles at 0.5C, and the capacity retention rate is 83.6%.
[0063] Example 5 The preparation of the negative electrode plate of Example 5 is as follows: 80 parts by weight of pure silicon powder, 20 parts by weight of hard carbon, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) are dispersed in butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform negative electrode slurry, and the above-mentioned negative electrode slurry is coated on a carbon-coated aluminum foil with an adjustable coating machine, and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a negative electrode plate based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0064] The rest is the same as Example 1.
[0065] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 30 μm, and the room temperature impedance value is 1.4 Ω•mm -1The calculated ionic conductivity is 2.73 mScm -1 .
[0066] The sulfide solid electrolyte film and the positive and negative electrode sheets based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 5 were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 600 cycles at 0.5C, and the capacity retention rate is 86.7%.
[0067] Example 6 The difference between Example 6 and Example 1 is that the sulfide solid electrolyte in Example 6 is Li 10 G 2 S 12 , the rest is the same as Example 1.
[0068] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 25 μm, and the room temperature impedance value is 0.8 Ω•mm -1 The calculated ionic conductivity is 3.98 mScm -1 .
[0069] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 6 was cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 750 cycles at 0.5C, and the capacity retention rate is 84.6%.
[0070] Example 7 The difference between Example 7 and Example 6 is that the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution of Example 7 is obtained by dissolving 45 parts by weight of ethylene-vinyl acetate copolymer and 55 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending, wherein the total mass of the composite binder accounts for 5 wt %. The others are the same as Example 6.
[0071] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 25 μm, and the room temperature impedance value is 0.9 Ω•mm -1 The calculated ionic conductivity is 3.54 mScm -1 .
[0072] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 7 was cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 750 cycles at 0.5C, and the capacity retention rate is 82.3%.
[0073] Example 8 The difference between Example 8 and Example 6 is that the positive electrode active material of Example 8 is LiNi 0.8 Co 0.1 Mn 0.1 O 2 , the rest is the same as Example 6.
[0074] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 25 μm, and the room temperature impedance value is 0.8 Ω•mm -1 The calculated ionic conductivity is 3.98 mScm -1 .
[0075] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 8 was cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; the assembled all-solid-state lithium battery can be stably cycled for 600 cycles at 1C, and the capacity retention rate is 81.6%.
[0076] Example 9 The ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution is obtained by dissolving 30 parts by weight of ethylene-vinyl acetate copolymer and 70 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending them, wherein the total mass proportion of the composite binder is 5 wt%.
[0077] The all-solid-state lithium battery of this embodiment includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer. The preparation methods of the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are as follows: (1) Preparation of sulfide solid electrolyte film: 99 parts by weight of Li 3 PS 4The electrolyte and 1 part by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 20 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform solid electrolyte slurry. The solid electrolyte slurry was coated on aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80 °C for 8 hours to obtain a sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder. The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 38 μm, and the room temperature impedance value is 2.5 Ω•mm -1 The calculated ionic conductivity is 1.94 mS cm -1 .
[0078] (2) Preparation of positive electrode: 70 parts by weight of LiCoO 2 , 30 parts by weight Li 3 PS 4 The electrolyte, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a positive electrode sheet based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0079] (3) Preparation of negative electrode sheet: 60 parts by weight of graphite, 40 parts by weight of Li 3 PS 4 The electrolyte, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform negative electrode slurry. The negative electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a negative electrode sheet based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0080] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 9 was cut into square slices with a side length of 20 mm using a square slicing tool with a side length of 20 mm; the assembled all-solid-state lithium battery can be stably cycled for 1000 cycles at 0.5C, and the capacity retention rate is 84.4%.
[0081] Example 10 The ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution is obtained by dissolving 40 parts by weight of ethylene-vinyl acetate copolymer and 60 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending them, wherein the total mass proportion of the composite binder is 5 wt%.
[0082] The all-solid-state lithium battery of this embodiment includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer. The preparation methods of the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are as follows: (1) Preparation of sulfide solid electrolyte film: 99 parts by weight of Li 3 PS 4 The electrolyte and 1 part by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 20 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in butyl butyrate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform solid electrolyte slurry. The solid electrolyte slurry was coated on aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80 °C for 8 hours to obtain a sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder. The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 38 μm, and the room temperature impedance value is 2.7 Ω•mm -1 The calculated ionic conductivity is 1.79 mS cm -1 .
[0083] (2) Preparation of positive electrode: 70 parts by weight of LiCoO 2 , 30 parts by weight Li 3 PS 4 The electrolyte, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in butyl butyrate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 90°C for 10 hours to obtain a positive electrode sheet based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0084] (3) Preparation of negative electrode sheet: 55 parts by weight of graphite, 35 parts by weight of Li 3 PS 4The electrolyte, 3 parts by weight of VGCF and 3 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 60 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in butyl butyrate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform negative electrode slurry. The negative electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 70°C for 10 hours to obtain a negative electrode sheet based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0085] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 10 was cut into square slices with a side length of 20 mm using a square slicing tool with a side length of 20 mm; the assembled all-solid-state lithium battery can be stably cycled for 1000 cycles at 0.5C, and the capacity retention rate is 81.8%.
[0086] Embodiment 11 The ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution is obtained by dissolving 40 parts by weight of ethylene-vinyl acetate copolymer and 60 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending them, wherein the total mass proportion of the composite binder is 5 wt%.
[0087] The all-solid-state lithium battery of this embodiment includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer. The preparation methods of the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are as follows: (1) Preparation of sulfide solid electrolyte film: 99 parts by weight of Li 7 P 3 S 11 The electrolyte and 1 part by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 20 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in butyl butyrate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform solid electrolyte slurry. The solid electrolyte slurry was coated on a PET film using an adjustable coater and transferred to a vacuum oven for vacuum drying at 80 °C for 8 hours to obtain a sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder. The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder was 35 μm, and the room temperature impedance value was 2.7 Ω•mm -1 The calculated ionic conductivity is 1.65 mS cm -1 .
[0088] (2) Preparation of positive electrode: 75 parts by weight of LiCoO 2 , 25 parts by weight Li7 P 3 S 11 The electrolyte, 1 part by weight of VGCF and 5 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 100 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in butyl butyrate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 12 hours to obtain a positive electrode sheet based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0089] (3) Preparation of negative electrode sheet: 60 parts by weight of graphite, 40 parts by weight of Li 7 P 3 S 11 The electrolyte, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in butyl butyrate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform negative electrode slurry. The negative electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 90°C for 8 hours to obtain a negative electrode sheet based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0090] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 11 was cut into square slices with a side length of 20 mm using a square slicing tool with a side length of 20 mm; the assembled all-solid-state lithium battery can be stably cycled for 800 cycles at 0.5C, and the capacity retention rate is 85.3%.
[0091] Example 12 The ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution is obtained by dissolving 30 parts by weight of ethylene-vinyl acetate copolymer and 70 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending them, wherein the total mass proportion of the composite binder is 5 wt%.
[0092] The all-solid-state lithium battery of this embodiment includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer. The preparation methods of the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are as follows: (1) Preparation of sulfide solid electrolyte film: 96 parts by weight of Li 7 P 2 S 8I electrolyte and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform solid electrolyte slurry. The solid electrolyte slurry was coated on aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80 °C for 8 hours to obtain a sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder. The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder was 28 μm, and the room temperature impedance value was 2.4 Ω•mm -1 The calculated ionic conductivity is 1.49 mS cm -1 .
[0093] (2) Preparation of positive electrode: 70 parts by weight of LiCoO 2 , 30 parts by weight Li 7 P 2 S 8 I electrolyte, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) are dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a positive electrode sheet based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0094] (3) Preparation of negative electrode sheet: 65 parts by weight of graphite, 35 parts by weight of Li 7 P 2 S 8 I electrolyte, 1 part by weight of VGCF and 5 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 100 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) are dispersed in sec-butyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform negative electrode slurry. The above negative electrode slurry is coated on a carbon-coated aluminum foil with an adjustable coater, and transferred to a vacuum oven at 80°C for vacuum drying for 10 hours to obtain a negative electrode sheet based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0095] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 12 was cut into square slices with a side length of 20 mm using a square slicing tool with a side length of 20 mm; the assembled all-solid-state lithium battery can be stably cycled for 1000 cycles at 0.5C, and the capacity retention rate is 80.5%.
[0096] Embodiment 13 The ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution is obtained by dissolving 50 parts by weight of ethylene-vinyl acetate copolymer and 50 parts by weight of polyvinylidene fluoride in sec-butyl acetate and blending them, wherein the total mass proportion of the composite binder is 5 wt%.
[0097] The all-solid-state lithium battery of this embodiment includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer. The preparation methods of the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are as follows: (1) Preparation of sulfide solid electrolyte film: 97 parts by weight of Li 5.4 PS 4.4 Cl 1.6 The electrolyte and 3 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 60 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in benzyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform solid electrolyte slurry. The solid electrolyte slurry was coated on a PET film using an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 8 hours to obtain a sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder. The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder was 20 μm, and the room temperature impedance value was 1.8 Ω•mm -1 The calculated ionic conductivity is 1.41 mS cm -1 .
[0098] (2) Preparation of positive electrode: 65 parts by weight of LiCoO 2 , 35 parts by weight Li 5.4 PS 4.4 Cl 1.6The electrolyte, 3 parts by weight of VGCF and 3 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 60 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in benzyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a positive electrode sheet based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0099] (3) Preparation of negative electrode sheet: 60 parts by weight of graphite, 40 parts by weight of Li 5.4 PS 4.4 Cl 1.6 The electrolyte, 2 parts by weight of VGCF and 4 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder (i.e., 80 parts by weight of ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder solution) were dispersed in benzyl acetate, and mechanically stirred and mixed in a closed container for 2 hours to obtain a uniform negative electrode slurry. The negative electrode slurry was coated on a carbon-coated copper foil with an adjustable coater and transferred to a vacuum oven for vacuum drying at 80°C for 10 hours to obtain a negative electrode sheet based on the ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder.
[0100] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder provided in Example 13 was cut into square slices with a side length of 20 mm using a square slicing tool with a side length of 20 mm; the assembled all-solid-state lithium battery can be stably cycled for 700 cycles at 0.5C, and the capacity retention rate is 86.5%.
[0101] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the binder of Comparative Example 1 is ethylene-vinyl acetate copolymer, and the rest is the same as Example 1.
[0102] The thickness of the prepared ethylene-vinyl acetate copolymer-based sulfide solid electrolyte film is 30 μm, and the room temperature impedance value is 1.5 Ω•mm -1 (See Figure 1 ), the calculated ionic conductivity is 2.55 mS cm -1 .
[0103] The sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer binder and the positive and negative electrode sheets provided in Comparative Example 1 were cut into square slices with a side length of 30 mm using a square slice tool with a side length of 30 mm; after the assembled all-solid-state lithium battery was cycled for 1000 cycles at 0.5C, the capacity retention rate was 39.1%, and the battery cycle performance was shown in FIG. Figure 3.
[0104] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the binder of Comparative Example 2 is polyvinylidene fluoride, and the rest is the same as Example 1.
[0105] The thickness of the prepared sulfide solid electrolyte film based on polyvinylidene fluoride binder is 30 μm, and the room temperature impedance value is 2.1 Ω•mm -1 (See Figure 1 ), the calculated ionic conductivity is 1.82 mS cm -1 .
[0106] The sulfide solid electrolyte film based on polyvinylidene fluoride binder and the positive and negative electrode sheets provided in Comparative Example 2 were cut into square slices with a side length of 30 mm using a square slice tool with a side length of 30 mm; after the assembled all-solid-state lithium battery was cycled for 1000 cycles at 0.5 C, the capacity retention rate was 7.9%, and the battery cycle performance was shown in FIG. Figure 4 .
[0107] from Figure 2 , Figure 3 and Figure 4 It can be seen that the all-solid-state lithium battery assembled with sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder and positive and negative electrode sheets has better cycle stability.
[0108] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in the preparation process of the positive electrode plate of Comparative Example 3, a single binder of ethylene-vinyl acetate copolymer is used, and the sulfide solid electrolyte film and the negative electrode plate use the composite binder of Example 1. The rest is the same as Example 1.
[0109] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 30 μm, and the room temperature impedance value is 1.4Ω•mm -1 The calculated ionic conductivity is 2.73 mS cm -1 .
[0110] The sulfide solid electrolyte film and the positive and negative electrode sheets provided in Comparative Example 3 were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; after the assembled all-solid-state lithium battery was cycled 1000 times at 0.5 C, the capacity retention rate was 45.6%.
[0111] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in the preparation process of the negative electrode plate of Comparative Example 4, ethylene-vinyl acetate copolymer is used as a single binder, and the sulfide solid electrolyte film and the positive electrode plate use the composite binder of Example 1. The rest is the same as Example 1.
[0112] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 30 μm, and the room temperature impedance value is 1.4 Ω•mm -1 The calculated ionic conductivity is 2.73 mScm -1 .
[0113] The sulfide solid electrolyte film and the positive and negative electrode sheets provided in Comparative Example 4 were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; after the assembled all-solid-state lithium battery was cycled 1000 times at 0.5 C, the capacity retention rate was 51.7%.
[0114] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in the preparation process of the negative electrode plate of Comparative Example 5, polyvinylidene fluoride single binder is used, and the sulfide solid electrolyte film and the positive electrode plate use the composite binder of Example 1. The rest is the same as Example 1.
[0115] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 30 μm, and the room temperature impedance value is 1.4 Ω•mm -1 The calculated ionic conductivity is 2.73 mScm -1 .
[0116] The sulfide solid electrolyte film and the positive and negative electrode sheets provided in Comparative Example 5 were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; after the assembled all-solid-state lithium battery was cycled 1000 times at 0.5 C, the capacity retention rate was 36.8%.
[0117] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that in the preparation process of the positive electrode plate of Comparative Example 6, a single binder of polyvinylidene fluoride is used, and the sulfide solid electrolyte film and the negative electrode plate use the composite binder of Example 1. The rest is the same as Example 1.
[0118] The thickness of the prepared sulfide solid electrolyte film based on ethylene-vinyl acetate copolymer / polyvinylidene fluoride composite binder is 30 μm, and the room temperature impedance value is 1.4 Ω•mm -1 The calculated ionic conductivity is 2.73 mScm -1 .
[0119] The sulfide solid electrolyte film and the positive and negative electrode sheets provided in Comparative Example 6 were cut into square slices with a side length of 30 mm using a square slicing tool with a side length of 30 mm; after the assembled all-solid-state lithium battery was cycled 1000 times at 0.5 C, the capacity retention rate was 42.3%.
[0120] It can be seen from the experimental results of Examples 1-13 and Comparative Examples 1-6 that one or more of the chemical formulas shown in Formula I, Formula II, and Formula III are used as sulfide solid electrolytes, and a blended polymer of ethylene-vinyl acetate copolymer and polyvinylidene fluoride in different mass ratios is used as a composite binder. The sulfide solid electrolyte film based on the composite binder can effectively improve the ionic conductivity of the sulfide solid electrolyte film, and the sulfide solid electrolyte film based on the composite binder and the positive and negative electrode sheets are assembled into an all-solid-state battery, which has excellent cycle stability.
[0121] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0122] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0123] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. An all-solid-state lithium battery containing a composite binder, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, wherein the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer all comprise a composite binder, and the composite binder is ethylene-vinyl acetate copolymer and polyvinylidene fluoride.
2. The all-solid-state lithium battery according to claim 1, characterized in that: In the composite binder, the mass ratio of ethylene-vinyl acetate copolymer to polyvinylidene fluoride is 0.1:99.9-99.9:0.
1.
3. The all-solid-state lithium battery according to claim 1, characterized in that: The positive electrode sheet includes a current collector and a positive electrode material layer located above the current collector, wherein the positive electrode material layer includes a positive electrode active material, a sulfide solid electrolyte, a conductive agent and a composite binder; The negative electrode plate comprises a current collector and a negative electrode material layer located above the current collector, wherein the negative electrode material layer comprises a negative electrode active material, a sulfide solid electrolyte, a conductive agent and a composite binder; The solid electrolyte layer includes a sulfide solid electrolyte and a composite binder.
4. The all-solid-state lithium battery according to claim 3, characterized in that: In the positive electrode material layer, the mass proportion of the composite binder is 0.1-10wt%; And / or, in the negative electrode material layer, the mass proportion of the composite binder is 0.1-10wt%; And / or, in the solid electrolyte layer, the mass proportion of the composite binder is 0.1-10wt%.
5. The all-solid-state lithium battery according to claim 3 or 4, characterized in that: In the positive electrode material layer, the mass proportions of the positive electrode active material, the sulfide solid electrolyte, and the conductive agent are 60-80wt%, 20-40wt%, and 0.5-5wt%, respectively; And / or, in the negative electrode material layer, the mass proportions of the negative electrode active material, the sulfide solid electrolyte, and the conductive agent are 50-70wt%, 30-50wt%, and 0.5-5wt%, respectively.
6. The all-solid-state lithium battery according to claim 3, characterized in that: The sulfide solid electrolyte is one or a mixture of sulfide solid electrolytes having the general formula I, II or III: Li 6±l P 1-e E e S 5-r R r X 1±t Formula I In formula I, 0≤l<1, 0≤e<1, 0≤r<1, 0≤t<1, E is one or more of Ge, Si, Sn, Sb, R is O and / or Se, and X is one or more of F, Cl, Br, I; Li 10±l Ge 1-g G g P 2-q Q q S 12-w W w Formula II In formula II, 0≤l<1, 0≤g≤1, 0≤q<2, 0≤w<1, G is Si and / or Sn, Q is one or more of Sb, As, Ti, and W is one or more of O, Se, F, Cl, Br, and I; (100 - x - y)Li2S·xP2S5·yM m N n Formula III In formula III, 0≤x<100, 0≤y<100, 0<x+y<100, 0≤m<4, 0≤n<6, M is one or more of Ge, Si, Sn, Sb, and N is one or more of Se, O, Cl, Br, and I.
7. The all-solid-state lithium battery according to claim 1 or 3, characterized in that: The preparation method of the solid electrolyte layer comprises the following steps: adding a composite binder solution and a sulfide solid electrolyte to an organic ester solvent, mixing them in a closed container, and dispersing them uniformly to obtain a sulfide solid electrolyte slurry; coating the sulfide solid electrolyte slurry on a substrate, drying it, and pressing it to obtain a sulfide solid electrolyte film; And / or, the method for preparing the positive electrode sheet comprises the following steps: adding raw materials for preparing the positive electrode material layer into an organic ester solvent, mixing in a closed container, and dispersing uniformly to obtain a positive electrode slurry; coating the positive electrode slurry on a substrate, drying it, and pressing it to obtain a positive electrode sheet; And / or, the method for preparing the negative electrode plate comprises the following steps: adding raw materials for preparing the negative electrode material layer into an organic ester solvent, mixing in a closed container, and dispersing evenly to obtain a negative electrode slurry; coating the negative electrode slurry on a substrate, drying it, and then pressing it to obtain a negative electrode plate.
8. The all-solid-state lithium battery according to claim 7, characterized in that: The thickness of the sulfide solid electrolyte film is 5-200 μm; the ionic conductivity of the sulfide solid electrolyte film at 25° C. is 0.01-10 mS cm -1 .
9. The all-solid-state lithium battery according to claim 7, characterized in that: The organic ester solvent is one or a mixture of ethyl acetate, benzyl acetate, sec-butyl acetate, butyl butyrate, isobutyl butyrate, isobutyl isobutyrate, and butyl isobutyrate; and / or, the mixing method in the closed container is a mixture of one or more of mechanical shaking, mechanical stirring, roller milling, ball milling, ultrasonic dispersion, and agate mortar grinding, and the mixing time is 0.1 to 6 hours; And / or, the substrate is one or more of aluminum foil, copper foil, steel plate, glass plate, PE substrate, PET substrate, or the substrate is an extended product of a coating on aluminum foil, copper foil, steel plate, glass plate, PE substrate or PET substrate.
10. The method for preparing an all-solid-state lithium battery containing a composite binder according to claim 1, characterized in that: The following steps are involved: The composite binder solution and the sulfide solid electrolyte are added to an organic ester solvent, mixed in a closed container, and dispersed uniformly to obtain a sulfide solid electrolyte slurry; the sulfide solid electrolyte slurry is coated on a substrate, dried, and pressed to obtain a sulfide solid electrolyte film; The raw materials for preparing the positive electrode material layer are added to an organic ester solvent, mixed in a sealed container, and dispersed evenly to obtain a positive electrode slurry; the positive electrode slurry is coated on a substrate, dried, and then pressed to obtain a positive electrode sheet; Adding raw materials for preparing the negative electrode material layer into an organic ester solvent, mixing in a closed container, and dispersing evenly to obtain a negative electrode slurry; coating the negative electrode slurry on a substrate, drying it, and pressing it to obtain a negative electrode sheet; The positive electrode sheet, sulfide solid electrolyte film and negative electrode sheet are cut into corresponding sizes and shapes, stacked and assembled in sequence to form an all-solid-state lithium battery.
Citation Information
Cited By
A composite binder composition, a composite binder and a method of preparing and using the same
CN122790569A
